2021
DOI: 10.1111/aogs.14100
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in preeclampsia complicated by eclampsia and pulmonary edema after delivery

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Women with hypertensive pregnancy disorders scored worse on all measures of speed processing (Digital Symbol Substitution Test mean score of hypertensive pregnancy = 41.2; normotensive pregnancy = 43.4), Trail Making Test mean seconds hypertensive (pregnancy = 45.1; normotensive pregnancy = 42.4) (Mielke et al, 2016). Furthermore, women with eclampsia or preeclampsia with pulmonary edema had lower scores on the MoCA cognitive test at the time of discharge compared to normotensive pregnant women or preeclampsia patients without severe symptoms (Bergman et al, 2021c). A recent study demonstrated that 15 years after a hypertensive pregnancy disorder (gestational hypertension or preeclampsia), significant impairments in working memory was observed in women with a history of hypertension during pregnancy (Adank et al, 2021).…”
Section: A History Of (Pre)eclampsia Is Associated With Cognitive Cha...mentioning
confidence: 99%
“…Women with hypertensive pregnancy disorders scored worse on all measures of speed processing (Digital Symbol Substitution Test mean score of hypertensive pregnancy = 41.2; normotensive pregnancy = 43.4), Trail Making Test mean seconds hypertensive (pregnancy = 45.1; normotensive pregnancy = 42.4) (Mielke et al, 2016). Furthermore, women with eclampsia or preeclampsia with pulmonary edema had lower scores on the MoCA cognitive test at the time of discharge compared to normotensive pregnant women or preeclampsia patients without severe symptoms (Bergman et al, 2021c). A recent study demonstrated that 15 years after a hypertensive pregnancy disorder (gestational hypertension or preeclampsia), significant impairments in working memory was observed in women with a history of hypertension during pregnancy (Adank et al, 2021).…”
Section: A History Of (Pre)eclampsia Is Associated With Cognitive Cha...mentioning
confidence: 99%
“…attention from clinicians. Bergman et al (2021) suggested that PE patients had lower MoCA scores than normotensive pregnant women when they presented with symptoms of eclampsia or pulmonary edema, while they found no difference in MoCA score between PE women without severe features and normotensive women. Our study found that PE patients had already developed cognitive impairment before severe complications.…”
Section: Discussionmentioning
confidence: 97%
“…Pre‐eclampsia with severe features, such as eclampsia and HELLP syndrome, has been associated with poorer cognitive performance 54 . These severe features may be associated with greater BBB leakage.…”
Section: Discussionmentioning
confidence: 99%